Advances in Computer Communication and Computational Sciences Proceedings of IC4S 2017, Volume 1 - Bhatia, Sanjiv K.; Tiwari, Shailesh; Mishra, Krishn K.; Trivedi, Munesh C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book includes the insights that reflect 'Advances in Computer and Computational Sciences' from upcoming researchers and leading academicians across the globe. It contains the high-quality peer-reviewed papers of 'International Conference on Computer, Communication and Computational Sciences (IC4S 2017), held during 11-12 October, 2017 in Thailand. These papers are arranged in the form of chapters. The content of this book is divided into two volumes that cover variety of topics such as intelligent hardware and software design, advanced communications, intelligent computing techniques, intelligent image processing, and web and informatics. This book helps the perspective readers' from computer industry and academia to derive the advances of next generation computer and communication technology and shape them into real life applications.
Preface -- About the Editors -- Table of Contents -- 38 papers -- Author Index.
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence